Women, medicine and science: Kansas female physicians 1880-1910 - Brackney, Gail Louise (Kansas State University, 1990)
Female physicians in the nineteenth century faced opposition from the medical profession and from societal norms that dictated specified roles for females in Victorian society. Females who practiced medicine in Kansas struggled with these problems which were manifest nationwide. They clung to traditional therapeutics compatible with their domestic role extended into the public sphere. The advent of new bacteriological principals seemed to contradict the justification women's place in medicine. Six female physicians were selected for this study to represent practitioners within the state. Their medical education patterns reflect the overall pattern in the state, and their practices spanned the years of the study, 1880 to 1910. Chosen for the study were Dr. Deborah K. Longshore, Dr. Maggie McCrea, Dr. Ida Barnes, Dr. Frances Storrs, Dr. Sara Greenfield, and Dr. Frances Harper. . .